The Impact of Leverage on Corporate Financial Performance: A Comprehensive Literature Review - Saleh, Nursahdi (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
Leverage is a critical concept in financial management that can significantly influence a company's capital structure and overall performance. Properly managed leverage can enhance a company's return on equity, but it also elevates the risk of bankruptcy if not handled with care. This literature review aims to provide a comprehensive analysis of the impact of leverage on corporate financial performance, drawing insights from recent studies and highlighting key factors that affect the effective use of leverage in various industrial contexts. Previous studies have shown that leverage can enhance operational efficiency and the productivity of invested capital, supporting corporate growth and value. However, improper leverage decisions can increase financial risk and instability. Additionally, the interaction between leverage, capital structure, and corporate governance highlights the importance of strategic financial planning and robust governance frameworks in optimizing financial outcomes. The relationship between leverage and corporate social responsibility (CSR) also demonstrates that well-managed leverage can amplify the positive effects of CSR initiatives on financial performance and risk management. This review provides valuable insights for academics and practitioners, identifying gaps in the literature and calling for more comprehensive and context-specific studies to further explore these dynamics.